Laboratory testing and numerical simulation of piezoelectric energy harvester for roadway applications. (15th August 2018) - Jasim, Abbas; Yesner, Greg; Wang, Hao; Safari, Ahmad; Maher, Ali; Basily, B.
Highlights: The energy output and mechanical failure of piezoelectric energy harvester is studied. The predicted voltage and power from numerical simulation match well with experimental measurements. The energy output increases with the increase of loading frequency and load magnitude. The performance of energy module is affected by fabrication of single transducer and packaging design. Abstract: The main objective of this study is to evaluate energy output and mechanical failure of piezoelectric energy harvester for roadway applications. The Bridge transducer with layered poling was designed to have high piezoelectric coefficient and capacitance. An energy harvester module that contains multiple stacked transducers was fabricated and tested under single pulse and cyclic loading events. Forensic analysis was conducted to investigate fatigue failure of piezoelectric transducers after repeated loading. Finite element simulation was used to evaluate output power and mechanical stress of energy harvesters with different layer thicknesses of epoxy adhesive, material types of packing material, and gap design. The predicted voltages and power outputs obtained from numerical simulation match well with experimental measurements. The energy output increased with the increase of loading frequency and load magnitude. This indicates that the energy harvesting performance is affected by vehicle weights, speed, and the embedment location of energy module. On the other hand, the resistive load can be optimized to increase the energy output. The analysis results showed that two different material failure models need to be considered in relation to mechanical failure of Bridge transducer, namely tensile and shear failure. It emphasizes that the optimum design of energy module should consider the balance of energy output and fatigue life that are affected by fabrication of single Bridge transducer and the packaging design of energy module.